SPRZECZNOŚĆ Z PRAWEM UNII EUROPEJSKIEJ JAKO PRZESŁANKA NIEWAŻNOŚCI CZYNNOŚCI PRAWNEJ NA PODSTAWIE ART. 58 K.C. - Gutowski, Maciej (Wydział Prawa i Administracji UAM, 2006)
The paper deals with the main provision of art. 58 § 1 of the civil law code concerning invalidity of a legal act. Since Poland’s accession to the European Union, the scope of that the provision has significantly broadened, and the catalogue of the sources of law provided in art. 87 of the Constitution can no longer be considered exhaustive. The paper analyses invalidity of a legal act arising from the fact that its contents or purpose are contrary to the Community law.
CONTRADICTION WITH EU LAW AS AN INHERENT FEATURE OF INVALIDITY OF A LEGAL ACT PURSUANT TO ARTICLE 58 OF THE CIVIL LAW CODE